Risk factors for central venous catheter-related infections in a neonatal population - systematic review - Viviane Rosado; Paulo A.M. Camargos; Lêni M. Anchieta; Maria C.F. Bouzada; Gabriela M. de Oliveira; Wanessa T. Clemente; Roberta M. de C. Romanelli (Elsevier, 2018)
Objective: This was a systematic review of the incidence density and risk factors for central venous catheter-related infections in a neonatal population. Data source: The MEDLINE, Embase, Cochrane, BDENF, SciELO, and LILACS databases were used without date or language restriction. Studies that analyzed risk factors for bloodstream infections in newborns were identified. Data synthesis: A total of 134 articles were found that met the eligibility criteria. Of these articles, 14 were selected that addressed risk factors for central venous catheter-related infection in neonates. Catheter-related bloodstream infections remain an important complication, as shown by the incidence rates reported in the studies included in this review. The observed risk factors indicate that low birth weight, prematurity, and longer catheter permanence are related to a higher incidence of bloodstream infections. It has been observed that low rates of catheter-related infections, i.e., close to zero, are already a reality in health institutions in developed countries, since they use infection surveillance and control programs. Conclusion: Catheter-related bloodstream infections still show high incidence density rates in developing countries. The authors emphasize the need for further longitudinal studies and the need for better strategies to prevent risk factors, aiming at the reduction of catheter-related infections. Resumo: Objetivo: Trata-se de uma revisão sistemática sobre a densidade de incidência e de fatores de risco para infecção associada a cateter venoso central em população neonatal. Fontes dos dados: Utilizou-se os bancos de dados Medline, Embase, Cochrane, Bdenf, Scielo, Lilacs, sem restrição de data ou de idioma. Identificaram-se os estudos que analisaram fatores de risco para infecção da corrente sanguínea em recém-nascidos. Síntese dos dados: Foram encontrados 134 artigos conforme os critérios de elegibilidade. Destes artigos, foram selecionados 14 que abordaram fatores de risco para infecção associada a cateter venoso central em neonatos. A infecção da corrente sanguínea associada a cateter continua a mostrar-se como uma importante complicação, conforme demonstram as taxas de incidência relatadas nos estudos incluídos nesta revisão. Os fatores de risco observados apontam que baixo peso ao nascer, prematuridade e maior tempo de permanência do cateter estão relacionados à maior incidência de infecção da corrente sanguínea. Observou-se que taxas de infecção associada a cateter em valores baixos, próximos a zero, já são uma realidade em instituições de saúde de países desenvolvidos, uma vez que utilizam programas de vigilância e controle de infecção. Conclusão: A infecção da corrente sanguínea associada a cateter ainda apresenta altas taxas de densidade de incidência em países em desenvolvimento. Destaca-se a necessidade de realização de mais estudos longitudinais e a necessidade de melhores estratégias de prevenção dos fatores de risco para a redução de infecção associada a cateter. Keywords: Catheter-related infections, Central venous catheterization, Risk factors, Palavras-chave: Infecções relacionadas a cateteres, Cateterismo venoso central, Fatores de risco